Prognosis of subglottic carcinoma: Is it really worse?. Issue 2 (26th June 2018) - Coskun, Hakan; Mendenhall, William M.; Rinaldo, Alessandra; Rodrigo, Juan P.; Suárez, Carlos; Strojan, Primož; López, Fernando; Mondin, Vanni; Saba, Nabil F.; Shaha, Ashok R.; Smee, Robert; Takes, Robert P.; et al.
Abstract: It is traditionally accepted that subglottic carcinoma has a worse prognosis than tumors arising in other subsites of the larynx, owing to its tendency to present in advanced stages, with a high incidence of cartilage invasion and extralaryngeal spread. The incidence of subglottic carcinoma varies among series, mainly because there is no uniform definition of the upper boundary of the subglottis. The extent of the tumor may be difficult to define because subglottic carcinoma may spread through the submucosa without visible mucosal changes. There is also a rich lymphatic network in the subglottis draining to the prelaryngeal and paratracheal lymph nodes, which are usually not involved by cancers arising in other laryngeal subsites. Current literature data indicates that early‐stage subglottic carcinoma can be treated using radiotherapy or chemoradiotherapy with high locoregional control and survival rates. In advanced stage subglottic carcinoma, combination of surgery followed by radiotherapy or chemoradiotherapy resulted in comparable outcomes, as in advanced carcinomas from the rest of the larynx. Stage for stage, it is likely that the prognosis for subglottic carcinoma and of glottic and supraglottic cancers is similar.